Pediatric Procedural Sedation in the Emergency Setting - Elizabeth A. Lucich, MD; Nicholas S. Adams, MD; Paige C. Goote, BS; John A. Girotto, MD, MMA; Ronald D. Ford, MD (Plastic and Reconstructive Surgery, Global Open, 2020)
Background:. Pediatric emergency department (ED) visits are common. Many are due to injury, which require procedural treatments with sedation. There are many well researched independent predictors of adverse events for pediatric procedural sedation. The duration of sedation as a predictor of adverse events has not been well studied. This study aims to determine the complication rate and severity of procedural sedation as well as determine if the duration of sedation is correlated with an increased risk of complications.